Plants and seeds - Stidworthy, John frey50 (Gloucester Press New York, 1990)
Text and microscopic photographs introduce various forms of plant life, their methods of reproduction, and their assimilation of nutrients.
Keywords: Botany -- Anatomy -- Juvenile literature; Plants -- Reproduction -- Juvenile literature; Photomicrography -- Juvenile literature